2022
DOI: 10.1021/acs.chemmater.2c02174
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Broadband Near-Infrared Luminescence with Zero-Thermal-Quenching in Garnet Y3In2Ga3O12:Cr3+ Phosphors

Abstract: Broadband near-infrared (NIR) light source based on phosphor-converted light-emitting-diode (pc-LED) is crucial for applications in medical diagnosis, food quality analysis, and night vision fields, motivating the development of highly efficient and thermal robust NIR phosphor materials. Herein, a novel Cr 3+ -doped garnet phosphor Y 3 In 2 Ga 3 O 12 :Cr 3+ emerges from a fundamental study of the Ln 3 In 2 Ga 3 O 12 (Ln = La, Gd, Y, and Lu) family. Upon 450 nm excitation, this material presents a broadband NIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 69 publications
3
67
0
Order By: Relevance
“…The red‐shift of emission spectra is caused crystal field weakening derived from gradual lattice expansion as an increase of temperature; while the broadening of emission spectra should be ascribed to the increased vibration amplitude of excited electrons induced by the enhanced electron‐lattice interaction with increasing temperature. [ 34,51,52 ] The integral intensity at 423 K (Figure 4c) of this material maintains 84.5% of the initial intensity at 298 K. This value is lower than the garnets Ca 3 Mg 0.99 Zr 0.99 Ge 3 O 12 :0.02Cr 3+ (87.9%) and Ca 3 Mg 0.99 Sn 0.99 Ge 3 O 12 :0.02Cr 3+ (89.8%) in this family, but much higher than the Cr 3+ ‐activated garnet materials with long‐wavelength (λ em ≥ 800 nm) emission (as listed in Table 2 ).…”
Section: Resultsmentioning
confidence: 78%
“…The red‐shift of emission spectra is caused crystal field weakening derived from gradual lattice expansion as an increase of temperature; while the broadening of emission spectra should be ascribed to the increased vibration amplitude of excited electrons induced by the enhanced electron‐lattice interaction with increasing temperature. [ 34,51,52 ] The integral intensity at 423 K (Figure 4c) of this material maintains 84.5% of the initial intensity at 298 K. This value is lower than the garnets Ca 3 Mg 0.99 Zr 0.99 Ge 3 O 12 :0.02Cr 3+ (87.9%) and Ca 3 Mg 0.99 Sn 0.99 Ge 3 O 12 :0.02Cr 3+ (89.8%) in this family, but much higher than the Cr 3+ ‐activated garnet materials with long‐wavelength (λ em ≥ 800 nm) emission (as listed in Table 2 ).…”
Section: Resultsmentioning
confidence: 78%
“…62 With the increase of the temperature, the excited electrons prefer to reach the intersection of the 4 T 2 and 4 A 2 energy levels of Cr 3+ and then return to the ground state by non-radiative transition rather than light emission due to the EPC effect. 59,63 The increase of temperature will intensify the EPC effect, leading to a reduction of energy transferred from Cr 3+ to Yb 3+ , resulting in the decrease of the Yb 3+ SWIR luminescence. Significantly, it can be found that the integrated SWIR emission intensity of the KYbP 2 O 7 :0.01Cr 3+ phosphor at 120 °C retains 55.6% of the room temperature SWIR luminescence intensity, which is better than those of most of the other AMP 2 O 7 compounds (for example, ∼30%@120 °C in LiScP 2 O 7 :Cr 3+ , 51%@100 °C in LiGaP 2 O 7 :Cr 3+ , 47.5%@100 °C in NaInP 2 O 7 :Cr 3+ , and 47%@100 °C in LiInP 2 O 7 :Cr 3+ ), 38,64–66 suggesting that the phosphor has a fairly good luminescence thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…With the further increase of the Cr 3+ doping content from 0.03 to 0.1, the lifetimes decrease rapidly from 0.43 to 0.21 ms, evidencing the enhanced nonradiative transition with higher Cr 3+ concentration. 59,60 With the increase of doping concentration, the curve slightly deviates from the single exponential function owing to the inequivalent Cr 3+ sites distributed in the octahedrons. 61 The internal and external quantum efficiencies of the KYbP 2 O 7 :0.01Cr 3+ phosphor are also measured to evaluate its SWIR photoluminescence performances as shown in Fig.…”
Section: Swir Photoluminescence Properties Of the Kybp 2 O 7 :Xcr 3+ ...mentioning
confidence: 98%
“…The IQE, l max and FWHM of this phosphor and some recently studied NIR phosphors are compared in Table 2. 4,6,12,17,31,[42][43][44][45][46][47]…”
Section: Fluorescence Spectroscopy Analysismentioning
confidence: 99%